The Impact of Designating a Sports Area in Sena Village, Batang Kuis District, Deli Serdang Regency on Regional Development - Torotodo Harefa; Abdi Sugiarto; Abdiyanto Abdiyanto (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
This study examines the impact of designating a sports area in Sena Village, Batang Kuis District, Deli Serdang Regency, on local regional development. The development of a sports area has significant potential to drive local economic growth, improve the quality of life for residents, and create new job and business opportunities. The study aims to identify the extent to which the presence of the sports area influences various aspects of regional development, including infrastructure, economy, and socio-cultural dynamics. The research employs a qualitative method with a descriptive approach. Data was collected through field observations, interviews with various stakeholders, including local residents, regional government officials, and local business owners, as well as relevant literature reviews. Additionally, data analysis was conducted to understand the relationship between the development of the sports area and its impact on regional development. The results indicate that the designation of the sports area in Sena Village has had a significant positive impact on regional development. Infrastructure around the area has improved, including roads, transportation, and public facilities that support accessibility to the sports area. Economic impact is evident from the increase in local tourist visits, which has led to higher incomes for the community, especially in the small and medium enterprise sectors. Furthermore, the sports area has contributed to an increase in social and cultural activities within the community, with numerous sports events and festivals held regularly.